Study on the Religious and Philosophical Thoughts of Xizi Pagodas in Hunan Province of China - He, Yiwen (Religions, 2024)
The Xizi Pagoda (惜字塔) is a form of traditional religious building used for burning “Paper with Characters (字纸)”, worshiping the gods, praying for blessings, revitalzing culture, and it is also an important material embodiment in the process of the development and evolution of religion in China, carrying China’s unique “Scholarly Culture (书香文化)”. This paper is the first study of the philosophy of religion of Xizi Pagodas (a vernacular stone religious architectural landscape). The research of the representative Xizi Pagodas in different parts of Hunan province were carried out to analyze the origin of Xizi Pagodas, cultural rituals, modeling paradigms, decorative art, and to explore the traditional Chinese religious and philosophical thoughts embedded in Xizi Pagodas through relevant literatures. The results show that Xizi Pagodas contain the religious concepts of “Confucianism, Buddhism and Taoism (儒释道)”: the emergence of Xizi Pagodas is connected to the development of Confucianism; Xizi Pagodas incorporate Buddhistic thoughts and inherit architectural features of Buddhist Pagodas; and the “Xizi (惜字)” ritual and images of deities on Xizi Pagodas are associated with Taoism. At present, the number of Xizi Pagodas is decreasing, and the remaining ones are in a serious state of dilapidation and disrepair, and the “Xizi” Culture is gradually being forgotten and fading away. This paper enriches the relevant research on the Xizi Pagodas and the “Xizi” Culture.